Numerical investigation of heat transfer and pressure drop in nuclear fuel rod with three-dimensional surface roughness. (November 2018) - Tikadar, Amitav; Najeeb, Umair; Paul, Titan C.; Oudah, Saad K.; Salman, Azzam S.; Abir, Ahmed M.; Carrilho, Leo A.; Khan, Jamil A.
Highlights: Numerically investigated the heat transfer and pressure drop in a three-dimensional surface roughness nuclear fuel rod. Heat transfer coefficient enhanced by 86% at Re = 4.18 × 10 5 compared to the smooth surface. Pressure drop increased by 15.75% within Re ranging 4.50 × 10 4 - 1.07 × 10 5 . Abstract: The paper focuses on the numerical studies of heat transfer and pressure drop in a simulated nuclear fuel rod with three-dimensional surface roughness. Two-dimensional numerical simulations utilizing SST k - ω turbulent model were performed to evaluate heat transfer and pressure drop on the smooth and rough section of the heater rod. The numerical results were compared with experimental data obtained from a heater element which simulates a single Inconel-Nickel fuel rod for pressurized water reactor (PWR). The length of the rod was 2152.6  mm, and an outer diameter 9.5 mm, of which the outer surface of a 304.8 mm long section of the Inconel fuel rod was modified with three-dimensional (Diamond-shaped blocks) surface roughness. The angle of corrugation for each diamond block was 45°, and the length of each side of the diamond block was 1 mm. The numerically computed local heat transfer coefficient, overall Nusselt number, and pressure drop across the test rod shows good agreement with the corresponding experimental results. For the simulated rough surface, heat transfer coefficient was enhanced by 86% at Re = 4.18 × 10 5 as compared to the smooth surface, and pressure drop was found to increase by 15.75% within Re range of 4.50 × 10 4 - 1.07 × 10 5 . Plausible reason of the heat transfer enhancement of the three-dimensional surface roughness was discussed in the paper.